UJI AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL DAUN KEMBANG TELANG (Clitoria ternatea L.) DENGAN METODE FRAP - Fidia Muh.Ilyas Fidia; Endah Dwijayanti; Hasyim Bariun (Cokroaminoto Journal of Chemical Science, 2023)
This research is about Antioxidant Activity Test of Kembang Telang (Clitoria ternatea L.) Leaf Ethanol Extract with Ferric Reducing Antioxidant Power (FRAP) Method. The purpose of this study was to determine the value of the antioxidant activity of the ethanol extract of butterfly pea leaves (Clitoria ternatea L.) using the FRAP method. The research method included extraction by maceration using 96% ethanol solvent, followed by antioxidant analysis using a Visible spectrophotometer at a wavelength of 689 nm. The results of the antioxidant activity test of the ethanol extract of butterfly pea leaves (Clitoria ternatea L.) were obtained with an IC50 value of 20.786 ± 0.014 ppm and ascorbic acid with an IC50 value of 8.131 ± 0.094 ppm indicating that the ethanol extract of butterfly pea leaves (Clitoria ternatea L.) has antioxidant activity in the category very strong.